The Effect of Whole Gut Irrigation on Contractile Responses of Guinea Pig Gallbladder, Ileum, and Tissue Cholecystokinin Levels - Türkmen, Feyza; Soyer, Tutku; Keskil, Zuhal; Kısa, Üçler; Aslan, Mustafa; Şenyücel, Mine; Çakmak, Murat (European Journal of Pediatric Surgery, 2014)
Aim An experimental study was performed to evaluate the effect of whole gut irrigation (WGI) solutions on contractile responses of the gallbladder and ileum and also on tissue cholecystokinin (CCK) levels.Materials and Methods Thirty guinea pigs were enrolled into five groups including control group (CG) and WGI group (saline physiologic [SP], Ringer lactated [RL], polyethylene glycol [PEG], and dibasic sodium phosphate [DNP]). After median laparotomy, the distal esophagus was ligated and SP, PEG, RL, and DNP infusions (2 mL/kg/min) were performed via gastric catheter until rectal discharge became clear in WGI groups. Ileum and gallbladder samples were obtained for in vitro and biochemical studies without irrigation in CG and after irrigation with different WGI solutions. Isolated ileum and gallbladder preparations were suspended in organ baths for contractile responses of carbachol and CCK. Also, biochemical analysis of tissue CCK levels was performed in ileum and gallbladder samples.Results In PEG group, gallbladder and ileum CCK levels were significantly higher than CG (p < 0.05). Also, DNP irrigation caused increased CCK levels in gallbladder samples (p < 0.05). In lower carbachol concentrations, PEG group showed increased contraction responses in gallbladder samples when compared with controls (p < 0.05). However, ileal responses to carbachol did not show any significant difference between groups, contraction responses to CCK was decreased in PEG group when compared with CG (p < 0.05).Conclusion Among WGI solutions, PEG caused the highest CCK levels in gallbladder and ileum samples. Different WGI solutions affected the contractile responses of gallbladder and ileum smooth muscles divergently. Increased levels of CCK in PEG group support the decreased contractile responses in ileum. Therefore, our results confirm that the effect of WGI on gallbladder and ileum contractility may be CCK related.
Keywords: whole gut irrigation; gallbladder; cholecystokinin